2013
DOI: 10.1371/journal.pone.0074528
|View full text |Cite
|
Sign up to set email alerts
|

A Small Volatile Bacterial Molecule Triggers Mitochondrial Dysfunction in Murine Skeletal Muscle

Abstract: Mitochondria integrate distinct signals that reflect specific threats to the host, including infection, tissue damage, and metabolic dysfunction; and play a key role in insulin resistance. We have found that the Pseudomonas aeruginosa quorum sensing infochemical, 2-amino acetophenone (2-AA), produced during acute and chronic infection in human tissues, including in the lungs of cystic fibrosis (CF) patients, acts as an interkingdom immunomodulatory signal that facilitates pathogen persistence, and host toleran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
58
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(67 citation statements)
references
References 93 publications
9
58
0
Order By: Relevance
“…Additionally, in a recent mouse study, acute P. aeruginosa colonization was demonstrated to induce insulin resistance and mitochondrial dysfunction in the skeletal muscles (Tzika et al . ). Additionally, no evidence is available concerning the effect of exercise training on the skeletal muscle metabolism in patients with CF with more severe disease and more systemic inflammation (Van de Weert‐van Leeuwen et al .…”
Section: Discussionmentioning
confidence: 97%
“…Additionally, in a recent mouse study, acute P. aeruginosa colonization was demonstrated to induce insulin resistance and mitochondrial dysfunction in the skeletal muscles (Tzika et al . ). Additionally, no evidence is available concerning the effect of exercise training on the skeletal muscle metabolism in patients with CF with more severe disease and more systemic inflammation (Van de Weert‐van Leeuwen et al .…”
Section: Discussionmentioning
confidence: 97%
“…Lipids are also considered to be useful biomarkers for conditions other than cancer. Studies investigated the viability of intramyocellular lipids (IMCLs) and other molecules as biomarkers in burn trauma and infections caused by Pseudomonas aeruginosa , an opportunistic pathogen commonly found in soil and water, that typically infects the human airway, urinary tract, burns, and wounds . In these studies, IMCLs showed significant increases with severity of the condition and could serve as biomarkers for grading the progression of a Pseudomonas aeruginosa infection as well as for the therapeutic effectiveness in burn trauma patients.…”
Section: Understanding Disease Mechanismsmentioning
confidence: 99%
“…Reduced contractile function of skeletal muscle has been demonstrated to accompany the down-regulation of SIRT1 and IRS1 [49]. Although further studies are required to dissect the physiological effects of SIRT1-mediated deacetylation of IRS1, phosphorylation of IRS1 at serine-307 is considered as a molecular event that precedes and associates with the development of glucose intolerance [50,51].…”
Section: Resveratrol May Confer Anti-hyperglycemic Effects Through Momentioning
confidence: 99%